The Impact of Human Resource Management Practices on Organisational Performance: A Case Study of Nile Petroleum Corporation - Kuot Bol Bol (Uganda Christian University, 2024)
Human resource management (HRM) is relevant in the success of an organization through effective recruitment, development, and retention of employees. The relationship between HRM practices and organizational performance has received significant scholarly attention in recent years. Factors such as recruitment and selection, training and development, performance appraisal, compensation management, employee relations, and organizational culture all impact the performance outcomes of an organization. This study aims to examine the impact of HRM practices on organizational performance through a case study of Nile Petroleum Corporation in South Sudan. The findings of this study may inform the development of better policies and practices in the oil sector and assist organizations in improving their operational efficiency and sustainability. The study used a methodology chosen to assess the effects of human resource management practices on organizational performance, using a simple random sampling and purposive sampling technique. Both primary and secondary sources of data were also utilized. The researcher collected data using a questionnaire tool and conducted validity and reliability tests. To ensure ethical compliance, the researcher sought approval for conducting the study and took measures to preserve the privacy and anonymity of participants. The study found that effective HR practices, such as recruitment and selection, compensation and benefits, and performance management, can improve employee satisfaction, retention rates, and overall organizational outcomes. Moreover, challenges such as keeping up with employment laws, providing adequate training, and handling employee grievances can influence the performance of an organization. The study found that effective recruitment, fair and competitive compensation, well-defined performance expectations and constructive feedback, employee engagement, and training and development programs are crucial for improving organizational performance. The study recommends that organizations should adopt policies and strategies that meet both local and international standards, provide adequate compensation, set SMART goals, provide feedback, invest in employee training, and maintain a positive organizational culture. The study suggested that HR practices should be tailored to specific challenges in the South Sudanese oil industry, such as political instability and security issues.
Undergraduate research